Influence of bimodal particle distribution on material properties of BaTiO3 fabricated by paste extrusion 3D printing. Issue 13 (1st July 2021) - Renteria, Anabel; Garcia, Luisa F.; Balcorta, Victor H.; Ortiz, Dayna; Delfin, Luis C.; Regis, Jaime; Marcos-Hernández, Mariana; Espalin, David; Tseng, Tzu-Liang (Bill); Lin, Yirong
Abstract: Barium titanate (BaTiO3 ) is a lead-free piezoelectric ceramic widely used in sensors and actuators applications. However, there are many manufacturing challenges to process BaTiO3 due to the brittle nature of ceramics. Most current sensors based on piezoelectricity are limited to mold shapes or flat 2D structures, which narrow their applications. Paste extrusion (PE) 3D printing technique allows the fabrication of complex geometry ceramics with less design limitations. However, the piezoelectric property of 3D printed ceramics is typically lower than those fabricated using traditional means due to lower density. Herein, a study to evaluate the influence of bimodal particle distribution on improving density and piezoelectricity of BaTiO3 ceramics fabricated using PE 3D printing is presented. 3D printed and compression pressed samples under the same mixing ratios were compared. The highest packing density was obtained using 50-50% vol. fraction of bimodal particles for both types of samples. A predictive model for packing density was validated by experimental results. The highest piezoelectric coefficient of 350 pC/N was obtained using 50-50% vol. bimodal particle distribution. This piezoelectric coefficient is 40% higher than the monodispersed sample using 100 nm particles with a piezoelectric coefficient of 250 pC/N.